Mallomonas gusakovii sp. nov. (Chrysophyceae, Synurales), a new species from Phu Quoc Island, Vietnam - Gusev, Evgeniy S.; Kapustin, Dmitry A.; Martynenko, Nikita A.; Guseva, Elena E.; Kulikovskiy, Maxim S. (Phytotaxa, 2019)
Mallomonas gusakovii sp. nov. is described from Vietnam based on silica-scale morphology studied by means of transmission and scanning electron microscopy. This species belongs to section Quadratae and is characterized by large and broad scales of three types with an internal reticulation, V-shaped rib and a forward projecting wing. Different types of the V-shaped rib in taxa from section Quadratae are discussed. Scales of Mallomonas gusakovii were found only in two sites in Phu Quoc Island, Southern Vietnam.